Modern Batik Painting in Contemporary Fine Arts: The Influence of Impressionist and Aquarelle Techniques - Christina Szabo (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
The present paper investigates the development of modern batik painting techniques as they have been adopted and transformed within the Western fine arts context, with particular attention to the influences of Impressionist and aquarelle (watercolor) painting traditions. Through a qualitative analysis of artistic practices, historical developments, and technical methodologies, this study examines how the traditional Indonesian wax-resist dyeing technique has been elevated from craft status to recognized fine art medium in Western artistic discourse. The research identifies key challenges facing batik as fine art, including material limitations, institutional recognition barriers, the craft-versus-art dichotomy, and the difficulties of achieving painterly effects comparable to established Western media. Results demonstrate that the cross-pollination between batik techniques and Impressionist color theory, as well as aquarelle layering methods, has produced a distinctive hybrid art form that challenges conventional boundaries between craft and fine art. The study concludes that batik painting, when informed by Western painterly traditions, represents a significant yet underappreciated contribution to contemporary fine arts practice.